2017
DOI: 10.1007/s00234-017-1870-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of parkinsonism by a combined use of diffusion kurtosis imaging and quantitative susceptibility mapping

Abstract: A quantitative assessment using DKI and QSM analyses, particularly MK-dMPR and MS-PUp values, can readily identify patients with parkinsonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 44 publications
5
39
1
Order By: Relevance
“…In patients with MSAc, an FA decrease and an MD increase in the pontine crossing tract and middle cerebellar peduncles have been found before the appearance of the hot cross bun sign (88,89). Using diffusion kurtosis imaging, Ito et al (90,91) described a ratio of midbrain tegmentum diffusion to pontine crossing tract diffusion to distinguish between patients with PSP, MSA or PD and controls (90,91). Interestingly, Juttukonda et al (92) also found an FA decrease in the pontine crossing tract in patients with essential tremor vs. PD (92).…”
Section: Advanced Diffusion Approachesmentioning
confidence: 99%
“…In patients with MSAc, an FA decrease and an MD increase in the pontine crossing tract and middle cerebellar peduncles have been found before the appearance of the hot cross bun sign (88,89). Using diffusion kurtosis imaging, Ito et al (90,91) described a ratio of midbrain tegmentum diffusion to pontine crossing tract diffusion to distinguish between patients with PSP, MSA or PD and controls (90,91). Interestingly, Juttukonda et al (92) also found an FA decrease in the pontine crossing tract in patients with essential tremor vs. PD (92).…”
Section: Advanced Diffusion Approachesmentioning
confidence: 99%
“…To identify changes in the whole-brain white matter between the PPD and non-PPD groups, we carried out voxel-wise statistical analysis of the MK, FA, and MD maps using tract-based spatial statistics (TBSS) implemented in Functional Magnetic Resonance Imaging of the Brain (FMRIB) Software Library 5.0.9 44 , 45 . Regarding the region of interest (ROI) analysis in the basal ganglia of the Johns Hopkins University Eve atlas 46 , MK, FA, and MD values of the caudate nucleus, putamen, globus pallidus, and thalamus were then automatically measured using coregistered ROIs 37 , 40 , 41 .…”
Section: Methodsmentioning
confidence: 99%
“…All subjects underwent MR examination using a 3T scanner (Trillium Oval, Hitachi, Ltd., Tokyo, Japan) with an eight-channel head coil. DKI/DTI source images were acquired using a single-shot spin-echo echo-planar imaging (EPI) method, with the following scan parameters, which were optimized 6 and used in previous studies 5,[7][8][9][10] : repetition time/echo time, 4500/110 ms; motion-probing gradients, 20 directions; bvalues, 0, 1000, and 2500 s/mm 2 ; field of view, 24 cm; matrix size, 128 × 128; reconstructed matrix size, 256 × 256; slice thickness, 3.0 mm without interslice gaps; number of slices, 36; number of excitations, 4; reduction factor of parallel imaging, 2; and acquisition time, 12 min, 18 s. Structural images, including three-dimensional T1-weighted, T2-weighted, and fluid-attenuated inversion recovery images, were also acquired.…”
Section: Tesla Mr Imagingmentioning
confidence: 99%
“…Diffusion metric maps, including MK, FA, and MD, were calculated using an in-house software program 11 that has been used in previous studies. 5,[7][8][9][10] In the present study, FA and MD values were calculated using DTI data only from b-values of 0 and 1000 s/mm 2 .…”
Section: Tesla Mr Imagingmentioning
confidence: 99%
See 1 more Smart Citation